The Effect of Super-Repressor IkB-Loaded Exosomes (Exo-srIκBs) in Chronic Post-Ischemia Pain (CPIP) Models - Ji Seon Chae; Hyunju Park; So-Hee Ahn; Eun-Chong Han; Yoonjin Lee; Youn Jin Kim; Eun-Jin Ahn; Hye-Won Oh; Hyun Jung Lee; Chulhee Choi; Youn-Hee Choi; Won-joong Kim (MDPI AG, 2023)
Complex regional pain syndrome (CRPS) is a condition associated with neuropathic pain that causes significant impairment of daily activities and functioning. Nuclear factor kappa B (NFκB) is thought to play an important role in the mechanism of CRPS. Recently, exosomes loaded with super-repressor inhibitory kappa B (Exo-srIκB, IκB; inhibitor of NFκB) have been shown to have potential anti-inflammatory effects in various inflammatory disease models. We investigated the therapeutic effect of Exo-srIκB on a rodent model with chronic post-ischemia pain (CPIP), a representative animal model of Type I CRPS. After intraperitoneal injection of a vehicle, Exo-srIκB, and pregabalin, the paw withdrawal threshold (PWT) was evaluated up to 48 h. Administration of Exo-srIκB increased PWT compared to the vehicle and pregabalin, and the relative densities of p-IκB and IκB showed significant changes compared to the vehicle 24 h after Exo-srIκB injection. The levels of several cytokines and chemokines were reduced by the administration of Exo-srIκB in mice with CPIP. In conclusion, our results showed more specifically the role of NFκB in the pathogenesis of CRPS and provided a theoretical background for novel treatment options for CRPS.